Influencia de la formulación del enunciado y del control didáctico sobre la actividad intelectual de los alumnos en la resolución de problemas - Langlois, F.; Gréa, J.; Viard, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
Using as reference the scientist instead of the expert for analysing the pupil's behaviour in problem solving, we proposed to students (17 years old) closed and open problems. The great diversity of the students' productions and their analysis in the theoretical framework of didactical contract, oblige us to build two analysis grids: one of the students' activities and the other one for the finalities which we attribute to those activities. We show how ranging the strategy of resolution depends on the text of the problem.